Severe scoliosis in an adolescent, benefits of early detection: a case report - Halawani, Motssim S. (International Journal of Advances in Medicine, 2019)
Presentations of scoliosis to primary health care physicians are not rare. Challenges may arise when it comes to screening and who require treatment once diagnosed. Idiopathic scoliosis is a three-dimensional spine and trunk deformity that is considered the most common form of scoliosis in children. It commonly does not cause symptoms and may be overlooked. However, if there was progressive deformity and it remained untreated, it may cause serious complications. Apart from medical concerns, emotional and cosmetic worries due to visible deformity may lead to psychological and social effects. Despite advances in understanding scoliosis, there are still controversies when it comes to optimal screening and treatment of this condition. This case is about a thirteen years old female who presented with intermittent back symptoms and was found to have a severe form of idiopathic thoracolumbar scoliosis. Through this case, author will be discussing different aspects of scoliosis (prevalence, screening, diagnosis, and treatment options) with emphasis on psychological support and guidance to the physician on how to overcome this challenge.